2013
DOI: 10.1186/2191-0855-3-12
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cultural conditions for conversion of glycerol to ethanol by Enterobacter aerogenes S012

Abstract: The aim of this research is to optimize the cultural conditions for the conversion of glycerol to ethanol by Enterobacter aerogenes S012. Taguchi method was used to screen the cultural conditions based on their signal to noise ratio (SN). Temperature (°C), agitation speed (rpm) and time (h) were found to have the highest influence on both glycerol utilization and ethanol production by the organism while pH had the lowest. Full factorial design, statistical analysis, and regression model equation were used to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…Maximum hydrogen was produced by these microorganisms using glucose as carbon source. But during crude glycerol fermentation, both E. aerogenes and C. butyricum mainly produced ethanol and 1,3-PD (Zeng, 1996;Gonzalez-Pajuelo et al, 2005;Ito et al, 2005;Nwachukwu et al, 2013). By using these microorganisms at higher concentration of crude glycerol, the yield of 1,3-PD and ethanol was maximum, but by using co-substrate, the contrasting results were obtained.…”
Section: Hydrogen Production At Optimum Conditionscontrasting
confidence: 46%
See 2 more Smart Citations
“…Maximum hydrogen was produced by these microorganisms using glucose as carbon source. But during crude glycerol fermentation, both E. aerogenes and C. butyricum mainly produced ethanol and 1,3-PD (Zeng, 1996;Gonzalez-Pajuelo et al, 2005;Ito et al, 2005;Nwachukwu et al, 2013). By using these microorganisms at higher concentration of crude glycerol, the yield of 1,3-PD and ethanol was maximum, but by using co-substrate, the contrasting results were obtained.…”
Section: Hydrogen Production At Optimum Conditionscontrasting
confidence: 46%
“…The reason of using ethanol and 1,3-PD data was to monitor the utilization of crude glycerol in presence of APH for increased H 2 production with minimum end-product formation. Ethanol and 1,3-PD are the most common metabolites of glycerol metabolism by E. aerogenes (Ito et al, 2005;Jitrwung and Yargeau, 2011;Nwachukwu et al, 2012Nwachukwu et al, , 2013 and C. butyricum (Zeng, 1996 Szymanowska-Powałowska, 2014). Ito et al (2005), indicated that a higher initial concentration of crude glycerol decreased the yield of H 2 and ethanol.…”
Section: Hydrogen Production At Optimum Conditionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Glycerol (1,2,3‐propanetriol) is a simple trivalent alcohol that results from the natural degradation of the glyceride component of plant cell wall phospholipids or reserve lipids of plant seeds (Roger et al ., ; Nwachukwu et al ., ). It is produced in major amounts during transesterification of vegetable oils and animal fats (Solomon et al ., ; Barbirato et al ., ,b, ; Colin et al ., ) and has wide applications in different industries such as food and drinks, toothpaste, cosmetics, toiletries, plastics, tobacco, pulp and paper, paint, leather and textile, pharmaceuticals and automotive (Choi, ; Nicol et al ., ; Rossi et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The economic value of industrial glycerol has decreased due to the surplus crude glycerol generated during biodiesel production, and it cannot be utilized directly in any industrial applications due to the presence of impurities. Furthermore, it cannot be directly released into the environment without treatment as the cost of such treatment is not economical (Nwachukwu et al ., ). Recently, fermentative conversion of crude glycerol into valuable products such as, e.g., bioethanol has gained interest for the development of biodiesel‐producing industries, and also for replacing conventional carbohydrate sugars used in industrial microbial fermentation processes to convert it into a broad range of value‐added organic products such as bioethanol (Dharmadi et al ., ; Rossi et al ., ).…”
Section: Introductionmentioning
confidence: 97%